2022
DOI: 10.1021/acs.cgd.2c00539
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Energetic Coordination Polymers as Flame Colorants: Intriguing Architecture and Excellent Performance

Abstract: A flexible and multifunctional 4-hydroxy-3,5-dinitropyrazole (DNPO) ligand was produced while seeking "green" energetic coordination polymers (ECPs). A series of alkali metal and alkaline earth metal ECPs of DNPO were successfully prepared and comprehensively characterized using elemental analysis, infrared spectroscopy, differential scanning calorimetry, and thermogravimetric analysis. All ECPs were characterized via single-crystal X-ray diffraction. They have high crystal densities ranging from 1.743 (ECP-6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In our previous work, our group developed a series of new pyrotechnics based on DNPO and DNP (Figure ). , However, during combustion testing, it was found that the characteristic color of DNPO exhibited low purity and poor brightness. To increase the combustion temperature of DNP-based metal salts, we introduced aluminum, while a combustible agent was also added to enhance its combustion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, our group developed a series of new pyrotechnics based on DNPO and DNP (Figure ). , However, during combustion testing, it was found that the characteristic color of DNPO exhibited low purity and poor brightness. To increase the combustion temperature of DNP-based metal salts, we introduced aluminum, while a combustible agent was also added to enhance its combustion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…6–12 Among them, energetic complexes (ECs) based on the coordination self-assembly of metal ions and nitrogen-rich ligands have the advantages of a high energy level, a large specific surface area and high gas production, thus receiving widespread attention in the field of energetic materials and combustion promoters. 9,13–21…”
Section: Introductionmentioning
confidence: 99%
“…Energetic complexes are typically produced in the following three forms (Figure A–C): (A) high-energy anion-metal-cation, (B) high-energy cation-metal-ion-oxygen-rich-anion, and (C) azole anion-heavy metal-cation-azide anion. The foregoing three types of complexes exhibit different characteristics in terms of their physicochemical properties, and of these, types A and B tend to form high-energy complexes with a high oxygen content; a majority of such complexes also have a high mechanical sensitivity, facilitating their use as primary explosives, oxidizer combustion promoters, or heat-resistant explosives. Furthermore, C-type complexes are more likely to form nitrogen-rich structures and exhibit favorable thermal stabilities.…”
Section: Introductionmentioning
confidence: 99%